Structural basis of human VANGL-PRICKLE interaction - Yanyi Song; Shuyi Jian; Junlin Teng; Pengli Zheng; Zhe Zhang (Nature Communications)
Abstract Planar cell polarity (PCP) is an evolutionarily conserved process for development and morphogenesis in metazoans. The well-organized polarity pattern in cells is established by the asymmetric distribution of two core protein complexes on opposite sides of the cell membrane. The Van Gogh-like (VANGL)-PRICKLE (PK) pair is one of these two key regulators; however, their structural information and detailed functions have been unclear. Here, we present five cryo-electron microscopy structures of human VANGL1, VANGL2, and their complexes with PK1 at resolutions of 2.2–3.0 Å. Through biochemical and cell imaging experiments, we decipher the molecular details of the VANGL-PK interaction. Furthermore, we reveal that PK1 can target VANGL-containing intracellular vesicles to the peripheral cell membrane. These findings provide a solid foundation to understand the explicit interaction between VANGL and PK while opening new avenues for subsequent studies of the PCP pathway.